2021
DOI: 10.3389/fcell.2021.668851
|View full text |Cite
|
Sign up to set email alerts
|

Markers and Reporters to Reveal the Hierarchy in Heterogeneous Cancer Stem Cells

Abstract: A subpopulation within cancer, known as cancer stem cells (CSCs), regulates tumor initiation, chemoresistance, and metastasis. At a closer look, CSCs show functional heterogeneity and hierarchical organization. The present review is an attempt to assign marker profiles to define the functional heterogeneity and hierarchical organization of CSCs, based on a series of single-cell analyses. The evidences show that analogous to stem cell hierarchy, self-renewing Quiescent CSCs give rise to the Progenitor CSCs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 160 publications
0
23
0
5
Order By: Relevance
“…CD44 is the main cell surface receptor of hyaluronan (HA), which is associated with the rapid remodeling of the matrix [48]. CD44 is a classic cancer stem cell marker [78] and it is closed related to TGF-β-induced EMT in the A549 cell line [79]. We detected a strong inhibition of CD44 expression in the A549 cell line after 72 h of SA treatment, while H1299 kept constant levels of the gene.…”
Section: Discussionmentioning
confidence: 81%
“…CD44 is the main cell surface receptor of hyaluronan (HA), which is associated with the rapid remodeling of the matrix [48]. CD44 is a classic cancer stem cell marker [78] and it is closed related to TGF-β-induced EMT in the A549 cell line [79]. We detected a strong inhibition of CD44 expression in the A549 cell line after 72 h of SA treatment, while H1299 kept constant levels of the gene.…”
Section: Discussionmentioning
confidence: 81%
“…It is well known that CSC stemness has been related to poor patient prognosis in several types of cancers [22][23][24] whose properties are driven by transcription factors, the most important being OCT4, Sox2, and Nanog [25]. In our breast cancer cell model, the expression of Cx46GFP increased mRNA levels of OCT4 and Sox2; however, the Nanog mRNA levels were unchanged (Figure 2A).…”
Section: Cx46 Increases the Expression Of Csc Related Genes And Funtional Characteristicsmentioning
confidence: 71%
“…In PC sections, 46% (± 15%) of cancer cells were CD44-positive ( Figure 1B and Supplementary Figure 1B ), indicating that nearly half of all PC tumor cells expressed this stem cell marker. Next, we analyzed CD133, which is also a transmembrane glycoprotein that is overexpressed in several cancers ( 39 ). In human PC sections, 5% (± 9%) of tumor cells were CD133-positive ( Figure 1B and Supplementary Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…These senescence escapers exhibit stem cell characteristics and express increased levels of the stem cell marker CD133 ( 53 ). CD133 upregulates the WNT signaling pathway via PI3K/AKT pathway, increasing stem cell properties ( 39 ). A recent study by the group of Clemens Schmitt showed that the chemotherapeutic Adriamycin (Doxorubicin) induced senescence in mouse lymphoma cells and that these senescent lymphoma cells expressed stem cell markers such as CD133 or CD44.…”
Section: Discussionmentioning
confidence: 99%